1994
DOI: 10.1530/eje.0.1300472
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bright light on circadian patterns of cyclic adenosine monophosphate, melatonin and cortisol in healthy subjects

Abstract: Bright light is known as a strong zeitgeber on human circadian rhythms and influences several endocrine and neuroendocrine functions. In the present study we examined the influence of a 3-h bright light stimulus, given at different times during the day (morning or evening), on circadian patterns of cyclic adenosine monophosphate (cAMP), melatonin and cortisol. Two groups of synchronized healthy volunteers (lights on: 05.00-23.00 h) were exposed to bright light (2500 lux) for 3 h over 6 days either in the morni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…It appears that, in both animals and humans, the evening melatonin production onset does not necessarily phase shift in parallel with the morning offset (28). The findings of Lemmer et al (27) that healthy individuals do not shift their melatonin phase when light is given in the evening but depressed patients phase shift when light is given either in the evening or in the morning would indicate a disturbance or instability of the evening melatonin onset oscillator in depression. Rao et al (29), on the other hand, found no significant effects of morning light treatment on melatonin rhythms in nonseasonal depressive patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It appears that, in both animals and humans, the evening melatonin production onset does not necessarily phase shift in parallel with the morning offset (28). The findings of Lemmer et al (27) that healthy individuals do not shift their melatonin phase when light is given in the evening but depressed patients phase shift when light is given either in the evening or in the morning would indicate a disturbance or instability of the evening melatonin onset oscillator in depression. Rao et al (29), on the other hand, found no significant effects of morning light treatment on melatonin rhythms in nonseasonal depressive patients.…”
Section: Discussionmentioning
confidence: 96%
“…Lemmer et al (27) showed a significant phase advance in the circadian rhythm of melatonin when bright light was given to young healthy individuals in the morning but not when given in the evening. The two oscillators hypothesis indicate a different regulatory mechanism for melatonin onset in the evening and for melatonin offset in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…MEL, a marker rhythm of the biological clock, did not show a typical circadian rhythm, with very low values during daytime and a prominent peak at night around 04:00 h [39] in the OSAS patients (Table 2). This disturbed pattern was observed both in untreated OSAS patients as well as after CPAP (Table 2).…”
Section: Plasma Norepinephrine and Melatoninmentioning
confidence: 98%
“…Timed exposure to bright light and darkness can rapidly phase shift the timing of rhythms controlled by the human circadian pacemaker (Czeisler et al, 1986(Czeisler et al, , 1989(Czeisler et al, , 1990Dijk et al, 1987Dijk et al, , 1989Broadway et al, 1987;Lewy et al, 1987;Honma and Honma, 1988;Shanahan and Czeisler, 1991;Minors et al, 1991;Van Cauter et al, 1993Foret et al, 1993b;Allan and Czeisler, 1994;Boivin et al, 1994;Jewett et al, 1994;Shanahan et al, 1997). However, estimation of those light-induced phase shifts has been largely based on phase assessments performed under controlled conditions before and after but not during the phase-resetting stimulus (Hansen et al, 1987;Broadway et al, 1987;Dijk et al, 1989;Rosenthal et al, 1990;Shanahan and Czeisler, 1991;Buresová et al, 1991;Campbell et al, 1993a;Foret et al, 1993a;Lemmer et al, 1994;Deacon and Arendt, 1994;Boivin and Czeisler, 1998;Zeitzer et al, 1997). Few studies have reported melatonin data collected throughout the entire resetting trial (Lynch et al, 1978;Bureošvá et al, 1991;Whitson et al, 1995;Laakso et al, 1993;Van Cauter et al, 1994); none of the three-cycle resetting trials have described data observed throughout the circadian resetting process due to masking effects that complicate the identification of the endogenous circadian components of various rhythms.…”
mentioning
confidence: 99%